Adaptation of QueremoSaber system to communicate with the platform of Paraguay’s government - Elizondo-Pérez, Melvin Alonso (2019)
QueremoSaber is a tool that facilitates requesting information to public entities in Paraguay.At the present time the system is not being used because of a change in law that states thatthere should only be a single, centralized platform for that purpose and under the government’scontrol. For this reason, QueremoSaber needs an adaptation to modify its behavior and interactwith the open data portal provided by the Paraguayan state. The paper seeks to explain howthis task was done, the process and all the necessary changes to meet this need, all of this aspart of a professional practice.